1938
DOI: 10.1037/h0056387
|View full text |Cite
|
Sign up to set email alerts
|

Delayed response and discrimination learning by chimpanzees.

Abstract: Reported in part before the Eastern Branch of the American Psychological Association, April 2, 1938: "Discrimination learning and delayed response to visual stimuli by chimpanzees," by A. H. Riesen and V. Nowlis; and before the Southern Society for Philosophy and Psychology, April 15, 1938: "Delayed response by chimpanzee to spatial versus non-spatial cues," by H. W. Nissen, A. H. Riesen, and V. Nowlis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
1

Year Published

1959
1959
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 16 publications
0
54
1
Order By: Relevance
“…The tasks on which sulcus principalis lesions have the greatest effect, namely delayed response and delayed alternation, may be viewed as the limiting cases of decreasing trials per problem; they are one trial discrimination (or discrimination reversal) problems (Nissen, Riesen, & Nowlis, 1938). It is thus possible that the delayed-response deficit and the deficit on "short" discrimination tasks have a common basis.…”
Section: Discussionmentioning
confidence: 99%
“…The tasks on which sulcus principalis lesions have the greatest effect, namely delayed response and delayed alternation, may be viewed as the limiting cases of decreasing trials per problem; they are one trial discrimination (or discrimination reversal) problems (Nissen, Riesen, & Nowlis, 1938). It is thus possible that the delayed-response deficit and the deficit on "short" discrimination tasks have a common basis.…”
Section: Discussionmentioning
confidence: 99%
“…Yerkes and Nissen (1939) found evidence of what they believed to be only rudimentary symbolic processes in chimpanzees. Nissen et al (1938) reported the results of several related experiments involving variations on basic discrimination learning between a white panel and a black panel, one ofwhich led to food. The idea was that the subjects would have to respond to the color ofthe stimulus, thus eliminating positional cues, as the positions were changed between baiting and the opportunity to respond.…”
Section: Symbolismmentioning
confidence: 99%
“…The idea was that the subjects would have to respond to the color ofthe stimulus, thus eliminating positional cues, as the positions were changed between baiting and the opportunity to respond. Nissen et al (1938) believed that a symbolic mechanism was necessary for the subjects to solve the problem as they did. However, they concluded that this mechanism is highly developed for spatial cues, but not for visual stimuli.…”
Section: Symbolismmentioning
confidence: 99%
See 2 more Smart Citations